Galactorrhea after breast augmentation: case report and literature review - Raphaela Silveira do Amaral; Erick Samuel Santos-Demello; Rodrigo Pinto Gimenez; Fernando Giovanetti Morano; Soraya Teresa Teixeira Cassitas Gonçalves; Tatiani Cerioni Toth (Revista Brasileira de Cirurgia Plástica)
Introduction: Augmentation mammoplasty is one of the most frequently performed surgeries in plastic surgery. Among its rarer occurrences are galactorrhea, spontaneous milk output by the papilla, and galactocele, a collection of milky material in the surgical bed. There is little literature on this extremely rare occurrence, and through this article, we conduct a literature review and report on a case operated in our service. Case Report: We present a case of a 35-year-old patient who underwent breast augmentation surgery via the inframammary fold, with an implant placed in the subglandular plane, which evolved, on the thirtieth postoperative day, with galactorrhea exteriorized through the incision, and we propose a treatment for such intercurrence. Six months after the operation, the breasts were symmetrical, without signs of contracture or additional alterations; the patient was satisfied with the result and without new episodes of galactorrhea or galactocele. Conclusion: Although rare, with an incidence of less than 1%, galactorrhea can occur as a postoperative complication, and knowledge about it, as well as the forms of treatment, will benefit both patient and surgeon.